Comparative Analysis between Slotless Axial Flux Permanent Magnet Motor with Equidirectional Toroidal Winding and Integral‐Slot Winding. Issue 12 (2nd August 2022) - Wei, Yanqi; Si, Jikai; Han, Yaofei; Li, Yingsheng; Gan, Chun
Abstract : Fractional slot concentrated winding (FSCW) is a kind of winding structure with few‐slots/coils multi‐poles. FSCW has the potential value of high torque density due to its short end‐winding and high slot fill ratio and is widely used in low‐speed direct‐drive application situations. However, compared with integral slot winding (ISW), the back EMF coefficient of FSCW is smaller, which leads to smaller output torque under the same condition. To improve the back EMF coefficient of FSCW, equidirectional toroidal winding (ETW) is proposed and applied to the dual rotor slotless axial flux permanent magnet motor (AFPM), in which the unit structure is three slots/coils two poles, and the ideal back EMF coefficient is the same as that of ISW. In this paper, firstly, the structure of ETW is introduced and its operating principle is analyzed. Then, compared with the AFPM with ISW, the open circuit and load characteristics of the AFPM with ETW under two conditions of the same wire gauge and the same coil width are analyzed respectively. The back EMF coefficient and output torque of ETW‐AFPM are similar to that of ISW‐AFPM under the same coil width. The back EMF coefficient and output torque of ETW‐AFPM are a little lower than that of ISW‐AFPM under the same wire gauge. Finally, the experimental results also validate the feasibility of AFPM with ETW and the correctness of the analysis results. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.